Levodopa-induced dyskinesia in Parkinson’s disease: an updated review of pharmacological treatments - Chen, Feifei; Zhou, Changqing (Frontiers in Aging Neuroscience, 2025)
Levodopa-induced dyskinesia (LID) remains one of the most disabling complications of long-term dopaminergic therapy in Parkinson’s disease. Despite decades of investigation, only amantadine has been established as the standard FDA-approved treatment, while istradefylline provides a complementary non-dopaminergic option. Most other candidate agents–including memantine, clozapine, and serotonergic or noradrenergic modulators–have shown inconsistent efficacy or safety limitations, underscoring persistent translational challenges between preclinical promise and clinical outcomes. In addition to pharmacological therapies, deep brain stimulation (DBS) serves as an established non-pharmacological intervention for advanced cases. This review systematically synthesizes current pharmacological strategies, consolidating evidence on mechanisms, efficacy, safety, and regulatory status. We further highlight failed or inconclusive trials, emphasize gaps in trial design and patient heterogeneity, and discuss emerging approaches such as individualized therapeutic frameworks, novel drug delivery systems, and AI-assisted drug discovery. Potential complementary pathways, including Traditional Chinese Medicine (TCM), are also briefly noted as alternative directions. By linking mechanistic insights with therapeutic evidence, this review provides an updated framework for optimizing LID management and guiding future research directions.